The Utilization of Social Media As a Means of Public Education in Digital-Based PKM Programs - Larisu, Zulfiah; Nasim, Abu Sahman; Nugroho, Agung Yuliyanto; Raule, Jean Henry (PT. Anagata Sembagi Education, 2025)
The development of social media as part of digital transformation has opened up new opportunities in community education efforts, especially through the Student Creativity Program (PKM). This study aims to examine the strategy of utilizing social media as an educational tool in digital-based PKM activities. Social media such as TikTok, Instagram, and Facebook are used strategically to reach various segments of society, taking into account generational characteristics, information needs, and socio-cultural contexts. A descriptive qualitative approach was used in this study, with data collection techniques through in-depth interviews with implementing students, supervising lecturers, and beneficiary communities. Data analysis was carried out thematically with source triangulation to maintain validity. The results of the study indicate that the integration of social media in PKM not only increases access to educational information but also strengthens community participation in the learning process. The success of the program is highly dependent on the design of content that is visually attractive, substantively contextual, and participatory in its implementation. However, challenges related to digital literacy, information credibility, and community involvement still need to be addressed through sustainable strategies. Thus, social media has the potential to be an effective educational platform if utilized critically, creatively, and collaboratively within the framework of digital-based community service.